The sleepwalking snowman - Miedoso, Andres (Miedoso, Andres. Desmond Cole ghost patrol, 2019)
Desmond and Andres face a snowman that was built by a schoolmate but seems to have a mind of its own, as well as a snowball-throwing bully.